Sub-acute Toxicity Assessment of Taxol Isolated From Fusarium Solani, an Endophytic Fungus of Taxus Brevifolia, in Wistar Rats and Analyzing Its Cytotoxicity and Apoptotic Potential in Lung Cancer Cells - Kuriakose, Gini C.; Arathi, B. P.; Divya Lakshmanan, Mangalath; Jiby, M. V.; Gudde, Ramachandra Subbaraya; Jayabhaskaran, C. (Frontiers in Oncology, 2020)
The limited availability of taxol from plant sources has prompted the scientific world to look for an alternative, as in the chemical synthesis of tissue cultures of the Taxus species, to meet the increasing demand for the drug. However, these alternative means are expensive or result in low yield. Previously, we have reported that Fusarium solani isolated from Taxus celebica produced taxol and its precursor baccatin III in liquid-grown cultures, and it exhibited promising anticancerous effects in certain cancer cell lines. In the present study, we examined the sub-acute toxicity of fungal taxol (FS) in Wistar rats according to the Organization for Economic Co-operation and Development (OECD) guidelines. The sub-acute oral administration of FS up to 500 mg/kg for a period of 28 days appears to be safe in rats and did not cause severe treatment-related toxicity or treatment-related death. The observed changes in body weight, histopathology, hematological and biochemical parameters, and organ weight were not significant compared to those in the control group of animals. The results suggest that FS is relatively safe when administered orally in rats. The antiproliferative and apoptosis-inducing activities were studied in A549 (human lung cancer) cell line. FS arrested the cells at S and G2/M phases, leading to apoptosis. The characteristic molecular signatures of apoptosis, such as externalized phosphatidyl serine, DNA fragmentation, and nuclear and chromatin condensation, were observed upon FS treatment. FS triggered the generation of reactive oxygen species in A549 cells and elicited cell death by both extrinsic as well as the mitochondria-mediated intrinsic pathway of apoptosis. These results indicate that endophytic fungi isolated from medicinal plants may serve as potential sources of anticancerous compounds with little side effects.